The Intricacies of Software Component Composition - Lahon, Maushumi; Sharma, Uzzal (International Journal of Computer Sciences and Engineering, 2015)
Components in Component Based Software Engineering (CBSE) are designed for composition and so it is an acceptable fact that, if composition of components becomes more and more error free and easy, the market acceptance and use of component based systems would increase and finally the objective of CBSE could be achieved. As components are prepared by third parties, their composition to build a system according to the requirement specification is a big challenge in the field of CBSE. Many works have been initiated and carried out in this area and many more are yet to be done to bring this area to maturity. Literature review in this area throws light into the various aspects and details that need to be considered in composition. Literature also highlights many approaches to composition and their areas of implementation. The paper attempts to present a review on different aspects of composition by considering the works proposed by various researchers in different areas of composition. Towards the end of the paper an attempt is made to narrow down and concentrate more on the mismatching aspect of composition with a basic concept of the adaptation technique.